Relapse of pemphigus vulgaris after topical application of ingenol mebutate. (1st August 2016) - Russo, I.; Ferrazzi, A.; Alaibac, M.
Summary: Ingenol mebutate is a recently approved topical agent for the treatment of actinic keratosis. Its most common adverse effects are transient local skin reactions. We report a 63‐year‐old white man who presented with a red–brownish crusted plaque involving the dorsum of his nose and an eroded area on his lower lip, which appeared soon after topical application of ingenol mebutate gel. Clinical, histological and immunopathological features were consistent with a diagnosis of pemphigus vulgaris (PV). To our knowledge, this is the first report of relapse of PV after topical application of ingenol mebutate gel. The temporal relationship between the application of the drug and the outbreak of PV supports the involvement of this agent in triggering the disease. It is plausible that ingenol mebutate may have induced the disease by its action on the production of proinflammatory cytokines.